Individual Correlates of Sleep Among Childbearing Age Women in Canada. Issue 5 (3rd September 2019) - Vézina-Im, Lydi-Anne; Lebel, Alexandre; Gagnon, Pierre; Nicklas, Theresa A.; Baranowski, Tom
ABSTRACT: Objective/Background : Women of childbearing age (WOCBA) may be at high risk for short or poor sleep. Yet few studies have focused on this population. The study objective was to identify individual correlates of sleep duration and quality among WOCBA. Participants : The sample consisted of 9, 749 WOCBA aged 18–44 years from the Canadian Community Health Survey 2011–2014. Methods : All variables were self-reported. Sleep duration was dichotomized as insufficient (< 7 hr/night) or adequate (≥ 7 hr/night). A composite score of sleep quality was dichotomized as having sleeping problems none/little or some/most/all the time. Age, ethnicity, level of education, household income, mood disorders, parity, geographical location, fruit and vegetable (FV) intake, physical activity, smoking and alcohol consumption were tested as correlates of sleep duration or quality using hierarchical logistic regression. Results : Ethnicity, parity, geographical location and smoking were correlates of sleep duration; this model discriminated 56.9% of WOCBA. Ethnic minorities, WOCBA with many children, living in urban areas and smoking were associated with lower odds of having adequate sleep duration. Ethnicity, level of education, mood disorders, geographical location, FV intake, and alcohol consumption were correlates of sleep quality; this model discriminated 59.0% of WOCBA. Ethnic minorities, lower level of education, mood disorders, living in urban areas, low FV intake, and alcohol consumption were associated with lower odds of having quality sleep. Conclusions : Some WOCBA may be more at risk for short or poor sleep based on their demographics and health behaviors. This can be used to identify which WOCBA are most in need of sleep interventions.